ROLL DYNAMIC COEFFICIENTS APPROACH OF DECAY TEST USING THE GENERALIZED REDUCED GRADIENT METHOD (GRG) - Hasanudin, Hasanudin; Zubaydi, Achmad; Aryawan, Wasis Dwi (Journal of Applied Engineering Science, 2023)
Sea transportation is the vehicle which dominant and vital in the world. The increasing number of ships, types, and uncertain climate change have caused many ship accidents that have caused loss of life and property. The International Maritime Organization (IMO) issued the latest regulation on the second generation of ship stability criteria based on the dynamic of ship roll motions. The survival of dynamic stability depends on the hydrodynamic coefficients, which numerical and experimental calculations can obtain. The problem is finding the hydrodynamic coefficients of the ship roll quickly and accurately from the experimental roll decay data. This paper uses the Generalized Reduced Gradient (GRG) optimization to find the roll motion coefficient with the objective function of a standard deviation. The results show that the roll decay experiment graph is close optimization for variations of the minimum standard deviation used: all data, maximum-minimum amplitude, maximum amplitude, and minimum amplitude. The most similar chart to the experiment is optimization using a standard deviation of maximum-minimum amplitude with the optimal objective function σ = 1.006776 closest σ=1; obtained variable 0.1087688 m; 3.00306E-05 m-ton-sec. Based on sensitivity tests for various scenarios, optimization with a standard deviation of maximum amplitude has a high sensitivity, so it is necessary to avoid or be careful in its use. Generally, the GRG optimization method has the advantage of finding the hydrodynamic roll coefficient quickly and accurately.
Keywords: ship, roll decay, hydrodynamic coefficients, optimization